Paradigma Pembelajaran Learning How to Learn, Learning How to Relearn, Learning How to Unlearn pada Pembelajaran PAI - I. Abidi, Fitran; Yahiji, Kasim (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
Paradigms in education must be dynamic and can change according to societal developments. Paradigm changes can occur through a learning process, either consciously or forcedly. The purpose of writing this article is to describe the learning paradigm of learning how to learn, learning how to relearn, learning how to unlearn in PAI learning. The research method used in this study is library research. The learning paradigm of learning how to learn, learning how to relearn, and learning how to unlearn is a comprehensive approach to learning Islamic Religious Education that emphasizes the importance of the learning process, relearning, and eliminating irrelevant understanding. In Islamic religious education learning, the learning how to learn, learning how to relearn, learning how to unlearn paradigm describes the importance of students' ability to learn effectively, be open to renewing their understanding, and be ready to let go of understanding that is no longer relevant or wrong in accordance with the principles -authentic Islamic principles. This concept allows students to become more adaptive learners, responsive to change, and able to apply religious teachings in their daily lives.